Conocimiento de la educación y función pedagògica: el sentido de la competencia profesional - Touriñán López, José Manuel (Teoría de la Educación. Revista Interuniversitaria, 2009)
This article carrys out the axe of discussion about the development of education as a subject of knowledge. In fact, the content focusses three basic questions: a) The distintion between cultural matters and education as a subject of knowledge. (Knowing disciplines and knowing education). b) Arguments about educational knowledge such as specialized one. c) Teaching centres for Educational Specialists.